Integrative Understanding of Emergent Brain Properties, Quantum Brain Hypotheses, and Connectome Alterations in Dementia are Key Challenges to Conquer Alzheimer's Disease - Kuljiš, Rodrigo O. (Frontiers in Neurology, 2010)
The biological substrate for cognition remains a challenge as much as defining this function of living beings. Here, we examine some of the challenges to understand normal and disordered cognition in humans. We use aspects of Alzheimer’s disease and related disorders to illustrate how the wealth of information at many conceptually separate, even decoupled, physical scales — in particular at the Molecular Neuroscience versus Systems Neuroscience/Neuropsychology levels — presents a challenge in terms of true interdisciplinary integration towards a coherent understanding. These unresolved dilemmas include critically the as yet untested Quantum Brain hypothesis, and the embryonic attempts to develop and define the so-called Connectome in humans and in non-human models of disease. To mitigate these challenges, we propose a scheme incorporating the vast array of scales of the space and time (space-time) manifold from at least the subatomic through cognitive-behavioral dimensions of inquiry, to achieve a new understanding of both normal and disordered cognition, that is essential for a new era of progress in the Generative Sciences and its application to translational efforts for disease prevention and treatment.